Definitions of Guidelines for Introducing an Integrated Management System to Small and Medium Sized Enterprises - Fassoula, Evagelia D. (Cranfield University, 1999)
To survive and achieve to develop their activities in an increasingly competitive environment, small and medium sized enterprises have to increase their competitiveness and, progressively, reduce their operational cost. It is therefore the objective of this research project to develop a flexible and unique management system for these enterprises to use to integrate all management systems or activities related to quality, safety and environmental issues and continuously improve their overall business performance and also to get prepared for certification according to the relevant international standards. The research project has been based on the edition of 2000 of the ISO 9001 standard: "Quality Management Systems - Requirements", the ISO 14001: 1996 standard: "Environmental Management Systems - Specification with Guidance for Use", the BS 8800: 1996 standard: "Guide to Occupational Health and Safety Management Systems" and the Business Excellence Model. The thesis author carried out a data collection procedure to determine the special characteristics of small and medium sized enterprises and to specify their needs for survival and development. The results of the research reinforced the conclusions of the relevant literature that was reviewed. The areas of literature examined related to quality management systems as platforms for integration, to safety and environmental management systems and to business process analysis and the conclusions were taken under consideration from a point of view of small and medium sized enterprises. The output of the research project is a practical guide for small and medium sized enterprises. It is a route-map of activities for the implementation of the integrated management system, incorporating tools addressing specific management areas using quality, safety and environmental issues to focus them. The route-map has the potential to integrate the overall management activities of an organization and has an internal metric mechanism to indicate the rate of integration. The tools of the route- map were partially implemented to two (2) SMEs, giving positive validation of the concepts. 1